Legal Consequences of Notarial Deeds Made Not In Accordance with The Provisions of Article 16 Paragraph (1) Letter M UUJN - Anada Safara; Amad Sudiro (Jurnal Syntax Transformation, 2024)
Notarial documents are important legal evidence, but their validity depends on the fulfillment of the provisions of the UUJN, especially Article 16 paragraph (1) letter m. This research aims to analyze the legal consequences of notarial deeds that do not comply with the provisions of Article 16 paragraph (1) letter m of the UUJN, as well as understand the responsibilities of notaries in ensuring the validity of the documents they create. This research uses a doctrinal approach by analyzing legal norms through a literature review of relevant literature and legal sources. The main focus is on the legal consequences of notarial deeds that do not comply with the provisions of Article 16 paragraph (1) letter m of the UUJN. The research found that a notarial document that is not read and signed in the presence of the parties involved potentially loses its evidentiary power and is considered an underhand deed. Notaries are fully responsible for this mistake, which can result in administrative, civil and criminal sanctions. The obligation to read the deed orally by the notary is essential to ensure that all parties understand the contents of the document and agree to its terms. Violation of this obligation not only harms the parties involved but also undermines the integrity of the notary profession. The conclusion of this study confirms that the fulfillment of the provisions of Article 16 paragraph (1) letter m of the UUJN is mandatory to maintain the validity of notarial deeds.